Prediction of fetal sex in cattle by testosterone levels in allantoic fluid - Bongso, Tuan Ariffeen; Basrur, P. K.; Younglai, E. V. (Society for Reproduction and Fertility, 1976)
The testosterone concentration in allantoic fluid between 90 and 150 days of gestation in cattle can be used to determine the fetal sex; values were 442 +/- 20-3 (S.E.M.) pg testosterone/ml for males fetuses and 215 +/- 8-2 pg/ml for female fetuses.